ҚАЗІРГІ ҚАЗАҚ ПОЭЗИЯСЫНДАҒЫ АҢСАУ САРЫНЫ - Гүлманат Әуелхан; Ләззат Әділбекова (Foundations and Trends in Research, 2025)
The article examines the unique style of poems by Kazakh poets of the twentieth century, where tradition and innovation intersect. Particular attention is paid to the poems of a prominent representative of Kazakh poetry, Zharken Bodesh, namely the theme of nostalgia for the homeland. Using the example of the poet’s poems, which have become widespread among the people and among Kazakhs abroad, the author focuses on the figurative aspects of the poet’s poetry, which, in comparison with classical poetry, is distinguished by the originality of techniques, richness of images and deep meaning, encouraging the younger generation to love their homeland, country, land